Karang Taruna Training in Processing Wood Waste Into Sellable Goods in Nagari Koto Baru Simalanggang District Limapuluh Kota - Utama, Rizky Indra; Andreas, Laras Oktavia; Jufri, Windry Novalia; Prima, Fani Keprila; Yandra, Muvi (Universitas Negeri Padang, 2024)
Nowadays, the opportunity to get a job is depend on education degree. Therefore, looking for job opportunities such as entrepreneurship is an alternative for people who have limited degree of education. The 50 kota sub-district is the area with the largest coconut plantations in the 50 kota district. Apart from producing coconuts for sale, coconut trees can also be used as material for making furniture. This is a business opportunity for residents by utilizing coconut tree waste and wood waste. The solution to this condition is to provide knowledge training to young people who are not yet working and wood business people in the area to be able to create innovative furniture products. Of course it has a connection in reducing the number of people who are not working. The use of wood waste that can be obtained from processing coconut trees that are quite old and cannot produce good coconuts, as well as other wood waste can be utilized by creating simple furniture/decoration products that have selling value. This can certainly be a business opportunity for the community/youth of Karang Taruna who have not/don't work to become competent entrepreneurs independently. PKM activities begin with conducting field observations, providing material regarding sources of wood waste, types of wood, marketing steps in selling furniture products and continue with providing training on how to process wood waste into simple furniture/decoration products. The implementation of the work is carried out directly by the community/youth of Karang Taruna, then an evaluation is carried out by looking at the results of the product work by looking at its attractiveness and aesthetics so that it can become an item of marketable value on the market.